Studies of Reduced Graphene Oxide and Graphite Oxide in the Aspect of Their Possible Application in Gas Sensors - Drewniak, Sabina; Muzyka, Roksana; Stolarczyk, Agnieszka; Pustelny, Tadeusz; Kotyczka-Morańska, Michalina; Setkiewicz, Maciej (Sensors (Basel, Switzerland), 2016)
The paper presents the results of investigations on resistance structures based on graphite oxide (GRO) and graphene oxide (rGO). The subject matter of the investigations was thaw the sensitivity of the tested structures was affected by hydrogen, nitrogen dioxide and carbon dioxide. The experiments were performed at a temperature range from 30 °C to 150 °C in two carrier gases: nitrogen and synthetic air. The measurements were also aimed at characterization of the graphite oxide and graphene oxide. In our measurements we used (among others) techniques such as: Atomic Force Microscopy (AFM); Scanning Electron Microscopy (SEM); Raman Spectroscopy (RS); Fourier Transform Infrared Spectroscopy (FT-IR) and X-ray Photoelectron Microscopy (XPS). The data resulting from the characterizations of graphite oxide and graphene oxide have made it possible to interpret the obtained results from the point of view of physicochemical changes occurring in these structures.